IMAJINASI DISTOPIA SEBAGAI IDE PENCIPTAAN KARYA SENI GRAFIS - Yustiana, Salsabilla; Mahendrapati, Alexander Nawangseto (TEXTURE Art and Culture Journal, 2024)
Dystopia is a literary genre that tells a story of a place where everything is very bad. Dystopia has several characteristics such as dehumanization and totalitarianism. Dystopia provides another perspective in dealing with various social phenomena or problems. This is called defamiliarization so it is considered important to be raised into a work. The stages of the process of creating this Final Assignment work are based on David Campbell's creative method formulation, namely, 1.) Preparation, 2.) Concentration, 3.) Incubation, 4.) Illumination (AHA!), 5.) Verification/Production. The technique used to realize the work is the printing technique in etching-aquatint with the form of landscape imagery. These works are a response to the author's experience in the form of reading activities and watching films which resulted in a series of graphic art works which are a series of dystopian stories that are intended to be conveyed to the public so that they can think critically and are expected to provide a new perspective in dealing with social phenomena related to dystopia.